Analisis Efisiensi Produktivitas Menggunakan Metode Overall Equipment Effectiveness Pada Industri Manufaktur Automotive Components di PT Kawasan Industri Modern Cikande Serang - Gilang Agusti; Budiharjo (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Production machine efficiency has become a crucial factor in determining competitiveness of automotive component manufacturing industry amid increasingly intense global competition. This research aims to analyze the productivity efficiency level of production equipment using Overall Equipment Effectiveness method at PT Kawasan Industri Modern Cikande Serang. Research focus is directed on injection molding machine type IM-450 which has the largest output contribution in automotive component production process. Data collection was conducted over a three-month period through direct observation and documentation of company production records including machine operating time, downtime, minor stoppage frequency, and product quality data. OEE method is used to measure three main components namely availability, performance, and quality as indicators of production machine utilization effectiveness. Research results show OEE value of 73.40% consisting of availability 85.51%, performance 88.44%, and quality 97.00%. This value is still below world class standard of 85% with a gap reaching 11.60%. Six big losses analysis identifies breakdown losses as the largest contributor at 35.2%, followed by setup and adjustment losses 29.6%, and reduced speed losses 20.8%. Improvement recommendations include implementing structured preventive maintenance, standardizing setup procedures using SMED method, intensive operator training, and applying stricter quality control to achieve optimal productivity improvement. Keywords: Productivity Efficiency, Overall Equipment Effectiveness, Automotive Components, Six Big Losses, Availability Abstrak Efisiensi produktivitas mesin produksi menjadi faktor krusial dalam menentukan daya saing industri manufaktur komponen otomotif di tengah persaingan global yang semakin ketat. Penelitian ini bertujuan untuk menganalisis tingkat efisiensi produktivitas peralatan produksi menggunakan metode Overall Equipment Effectiveness di PT Kawasan Industri Modern Cikande Serang. Fokus penelitian diarahkan pada mesin injection molding tipe IM-450 yang memiliki kontribusi output terbesar dalam proses produksi komponen otomotif. Pengumpulan data dilakukan selama periode tiga bulan melalui observasi langsung dan dokumentasi catatan produksi perusahaan yang mencakup waktu operasi mesin, downtime, frekuensi minor stoppage, dan data kualitas produk. Metode OEE digunakan untuk mengukur tiga komponen utama yaitu availability, performance, dan quality sebagai indikator efektivitas penggunaan mesin produksi. Hasil penelitian menunjukkan nilai OEE sebesar 73,40% yang terdiri dari availability 85,51%, performance 88,44%, dan quality 97,00%. Nilai tersebut masih berada di bawah standar world class sebesar 85% dengan gap mencapai 11,60%. Analisis six big losses mengidentifikasi breakdown losses sebagai kontributor terbesar dengan 35,2%, diikuti setup and adjustment losses 29,6%, dan reduced speed losses 20,8%. Rekomendasi perbaikan mencakup implementasi preventive maintenance terstruktur, standardisasi prosedur setup menggunakan metode SMED, pelatihan intensif operator, serta penerapan quality control yang lebih ketat untuk mencapai peningkatan produktivitas optimal. Kata kunci: Efisiensi Produktivitas, Overall Equipment Effectiveness, Komponen Otomotif, Six Big Losses, Availability.